Nitrogen acquisition and resource allocation strategies in temperate seagrass Zostera nigricaulis: Uptake, assimilation and translocation processes. Issue 1 (December 2018) - Nayar, S.; Loo, M.; Tanner, J.; Longmore, A.; Jenkins, G.
Abstract The dominant seagrass in Port Phillip Bay (PPB), Australia, Zostera nigricaulis, declined between 2000 and 2011, coinciding with the 'Millennium drought' that ended in 2009. These seagrasses are nitrogen-limited, underpinning the need to develop nitrogen budgets for better ecosystem management. Environmentally realistic measurements of specific uptake rates and resource allocation were undertaken to develop nitrogen budgets and test the hypothesis that the above-ground and below-ground compartments are able to re-mobilise ammonium and nitrate through uptake, translocation and assimilation to adapt to varying levels of nitrogen in the ecosystem. Uptake of15 N labelled ammonium and nitrate by above- and below-ground seagrass biomass, epiphytes and phytoplankton was quantified in chambersin situ . Preferential uptake of ammonium over nitrate was observed, where the uptake rate for nitrate was about one sixth of that for ammonium. Epiphytes and phytoplankton also registered an increased affinity for ammonium over nitrate. Translocation experiments demonstrated the uptake by both the above-ground and below-ground biomass, respectively from the water column and pore water, and subsequent translocation to the opposite compartment. Acropetal translocation (below- to above-ground biomass) was more prevalent than basipetal translocation. This is a unique outcome given basipetal translocation has been widely reported forZostera by other researchers.